Heterogeneous distribution of H2O in the Martian interior: Implications for the abundance of H2O in depleted and enriched mantle sources. (17th April 2016) - McCubbin, Francis M.; Boyce, Jeremy W.; Srinivasan, Poorna; Santos, Alison R.; Elardo, Stephen M.; Filiberto, Justin; Steele, Andrew; Shearer, Charles K.
Abstract: We conducted a petrologic study of apatite within 12 Martian meteorites, including 11 shergottites and one basaltic regolith breccia. These data were combined with previously published data to gain a better understanding of the abundance and distribution of volatiles in the Martian interior. Apatites in individual Martian meteorites span a wide range of compositions, indicating they did not form by equilibrium crystallization. In fact, the intrasample variation in apatite is best described by either fractional crystallization or crustal contamination with a Cl‐rich crustal component. We determined that most Martian meteorites investigated here have been affected by crustal contamination and hence cannot be used to estimate volatile abundances of the Martian mantle. Using the subset of samples that did not exhibit crustal contamination, we determined that the enriched shergottite source has 36–73 ppm H2 O and the depleted source has 14–23 ppm H2 O. This result is consistent with other observed geochemical differences between enriched and depleted shergottites and supports the idea that there are at least two geochemically distinct reservoirs in the Martian mantle. We also estimated the H2 O, Cl, and F content of the Martian crust using known crust‐mantle distributions for incompatible lithophile elements. We determined that the bulk Martian crust has 1410 ppm H2 O, 450 ppm Cl, and 106 ppm F, and Cl and H2 O are preferentially distributed toward the Martian surface. The estimate of crustal H2 O results in a global equivalent surface layer (GEL) of 229 m, which can account for at least some of the surface features on Mars attributed to flowing water and may be sufficient to support the past presence of a shallow sea on Mars' surface.